The implication of online marketing strategies on consumers' decision-making process in Malaysia - Ahmad Saifuddin, Ahmad Daniel Haiqal; Ahmad, Siti Yuliandi (Malaysia Consumer and Family Economy Association (MACFEA), 2021)
Marketing can be considered crucial in today’s modern world due to increased competition in technological advancements. Online platforms have permitted the evolution of online marketing strategies. Everything is now available online, with applications and websites allowing consumers to shop at their leisure and in their time zone. With both advancements in technology between online marketing and online purchasing, and thus the objective of this paper is to find the relationship between online marketing strategies and consumers’ decision-making process in Malaysia. The focus of this study is to 1) to identify consumers’ perspectives on existing strategies of online marketing, 2) to investigate the relationship between online marketing strategies and consumers’ decision-making process in Malaysia and 3) to examine the most significant online marketing strategies in influencing consumers’ decision-making process in Malaysia. The target respondents of this study were Malaysian youth who have had engaged in purchasing or buying through an online medium to understand what kind of marketing is being used to make that decision. Online questionnaires have been distributed to Malaysians, specifically those who had experience purchasing online. The quantitative data were then analysed through descriptive, Pearson Correlation and Multiple Regression analysis using IBM SPSS. The Pearson results showed social media (r =0.369, p =0.01) and online advertisement (r = 0.298, p = 0.01) have a weak relationship towards consumers’ decision-making process while electronic words of mouth have a moderate relationship with consumer’s decision-making process with r = 0.441, p = 0.01. The Multiple Regression analysis also showed that electronic words of mouth (p < 0.005, B = 0.322) give the highest influence factor toward consumers’ decisionmaking process. The research will help researchers and business operators to understand the youth decision-making process better. Online marketing provides customers with more information while helping lower prices and growing companies across the globe. This buying behaviour can benefit both business operators and researchers to further enhance their knowledge for better marketing strategies in the future.